Improving specific class mapping from remotely sensed data by Cost-Sensitive learning - Silva, Joel (2019)
Silva, J., Bacao, F., Dieng, M., Foody, G. M., & Caetano, M. (2017). Improving specific class mapping from remotely sensed data by Cost-Sensitive learning. International Journal Of Remote Sensing, 38(11), 3294-3316. https://doi.org/10.1080/01431161.2017.1292073